2008
DOI: 10.1007/s00276-008-0442-2
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations in the branches of the human aortic arch in 633 angiographies: clinical significance and literature review

Abstract: Despite the fact that the variations in question are usually asymptomatic, they may cause dyspnea, dysphagia, intermittent claudication, misinterpretation of radiological examinations and complications during neck and thorax surgery. Furthermore, these variations may be accompanied by other congenital abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
171
5
32

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(245 citation statements)
references
References 22 publications
23
171
5
32
Order By: Relevance
“…In present study, origin of brachiocephalic trunk and left common carotid artery as separate branches was seen in 80%; in 20% brachiocephalic trunk and the left common carotid had a common trunk. This finding was nearly similar to that of Haifa A. Alsaif and Wafaa S. Ramadan [15 ], Suresh et al [14] where 83% had origin of brachiocephalic trunk and left common carotid artery as separate branches and 17% had common trunk of origin for both brachiocephalic trunk and left common carotid artery. Various studies have documented different incidences of this variation in different population (Table 1).…”
Section: Discussionsupporting
confidence: 77%
“…In present study, origin of brachiocephalic trunk and left common carotid artery as separate branches was seen in 80%; in 20% brachiocephalic trunk and the left common carotid had a common trunk. This finding was nearly similar to that of Haifa A. Alsaif and Wafaa S. Ramadan [15 ], Suresh et al [14] where 83% had origin of brachiocephalic trunk and left common carotid artery as separate branches and 17% had common trunk of origin for both brachiocephalic trunk and left common carotid artery. Various studies have documented different incidences of this variation in different population (Table 1).…”
Section: Discussionsupporting
confidence: 77%
“…This report is concerned with the "Adachi TYPE C" variation in which a fourth vessel, an anomalous left vertebral artery, also arises from the aortic arch. The frequency of this variation has generally been reported between 0.68% and 5.8% [2][3][4][5][6][7]. Two additional studies have reported frequencies of 7.41% and 15.3% [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…El desconocimiento de las expresiones variantes de las ramas derivadas del AA puede precipitar la ocurrencia de iatrogenias durante los procedimientos quirúrgicos (Matula et al;Satyapal et al;Nayak et al, 2006;Jakanani & Adair). La evaluación de la emergencia de las ramas del AA ha sido sido realizada en grupos poblacionales variados y a través de métodos anatómicos convencionales e imagenológicos (De Garis et al, 1933;Grande et al, 1995;Satyapal et al;Bathia et al;Yamaki et al;Berko et al;Natsis et al, 2009;Bhattarai & Poudel, 2010;Ogeng'o et al, 2010;Alsaif & Ramadan). Consideramos importante una caracterización morfológica de estas estructuras, desarrollada en material cadavérico fresco, que contemple población colombiana y que contribuya a la obtención de una casuística propia de referencia, al mejoramiento de la interpretación de sus imágenes y al manejo de eventos quirúrgicos.…”
Section: Introductionunclassified